Correction: Supramolecular metalloglycodendrimers selectively modulate lectin binding and delivery of Ru(ii) complexes into mammalian cells. Issue 46 (14th November 2016) - Bavireddi, Harikrishna; Murthy, Raghavendra Vasudeva; Gade, Madhuri; Sangabathuni, Sivakoti; Kikkeri, Raghavendra
Abstract : Correction for 'Supramolecular metalloglycodendrimers selectively modulate lectin binding and delivery of Ru(ii ) complexes into mammalian cells' by Harikrishna Bavireddi, et al., Org. Biomol. Chem., 2016, DOI: 10.1039/c6ob01546h.